Analysis of the Influence of Motivation and Work Discipline on Employee Performance Mediated by Organizational Commitment - Sholikhah, Sholikhah; Rachma Dania, Rizki Firdausi; huzaini, Moh; Putri Abudullah, Amelia; Chairunisa, Firda (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
This study aims to determine the performance of PT Wisata Borobudur Indah employees reviewed from the perspective of work motivation and work discipline and mediated by organizational commitment. The methods used were descriptive and explanatory with a population of 177 respondents and a sample of 123 employees were taken randomly and data was obtained by spreading questionnaires. The data obtained was processed to analyze to find out the picture of the research object and with SPSS, Lisrel and Path analysis software. The results of processing and statistical analysis show the results that, a). Motivation has a significant effect on Organizational Commitment with a path coefficient of 0.278. b). Work Discipline has a significant effect on Organizational Commitment with a path coefficient of 0.217. c). Motivation has a significant effect on Performance with a path coefficient of 0.184. d). Work Discipline has a significant effect on Performance with a path coefficient of 0.248. e). Organizational Commitment has a significant effect on Performance with a path coefficient of 0.325 Path coefficient. f). Motivation has a significant effect on Performance through Organizational Commitment with a path coefficient of 0.090. g). Work Discipline has a significant effect on Performance through Organizational Commitment with a path coefficient of 0.071.